SAW-TOOTHED PATTERN OF RELATIVE PALEOINTENSITY RECORDS AND CUMULATIVE VISCOUS REMANENCE - Kok Y.S.; Tauxe L. (My University, 1996)
Several studies of relative paleointensity data derived from marine sediments spanning the last 4 Myr display an asymmetrical ''saw-toothed'' pattern. Polarity reversals of the geomagnetic field are associated with low points in paleofield intensity, preceded by a long-term progressive decay of the field and followed by a rapid post-transitional recovery. Since similar behavior is observed in far-flung sites whose rock magnetic records are different, it is argued that the world-wide ''saw-toothing'' represents geomagnetic field behavior. We present an alternative explanation, calling on the effect of ''hard'' viscous remanence.